Prevalensi Hasil Pemeriksaan HBsAg dan Anti HBs pada PSK (Pekerja Seks Komersial) - Priyatno, Djoko; Qomariyah, Nurul (Poltekkes Kemenkes Semarang, 2019)
Commercial sex workers are a high risk group of STD infection (HIV-AIDS, syphilis, gonorrhea and Hepatitis-B). Transmission of HBV 100x faster than the HIV. Diagnosis HBsAg and Anti-HBs is a marker of HBV infection can be detected at least 2 weeks before clinical symptoms appear. The incidence of STIs Semarang (in 2012) is the highest in the resocialization Argorejo as much as 1,623 cases. Monitoring of Hepatitis B in resocialization has not become a routine examination. The formulation of the research problem is